Question 2 Part A: Three equations that all represent the same function f are shown. Select the equation

Question 2 Part A: Three equations that all represent the same function f are shown. Select the equation that includes the value of f(0) as a number that appears in the equation.
Part B: Identify f(0)
Part A: (select all that apply)
F(x) = 2(x + 3) - 8
f(x) = 2x^2+ 12x + 10
f(x) = 2(x + 5)x + 1)
Part B:(select all that apply)
-10
-8
-5
-3
-1
0
35
00
10

Related Posts

This Post Has 6 Comments

  1. I'll focus on one example:    f(x)=x^2:    (-2,f(-2)) and (0,f(0)) 4)

    Find the average rate of change of f(x) = x^2 from x = -2 to x = 0:
               f(0) - f(-2)           (0)^2 - (-2)^2)         0-4
    arc = =  = = -2 (answer)
                  0-(-2)                         2                    2

  2. Substitute the values of x to the equation of a function f.

    f(x) = x - 5

    f(-1) = -1 - 5 = -6 ≠ 0

    f(0) = 0 - 5 = -5 ≠ 3

    f(1) = 1 - 5 = -4   🙂

    f(2) = 2 - 5 = -3   🙂

    f(5) = 5 - 5 = 0 ≠ -5

    f(8) = 8 - 5 = 3 ≠ -6

  3.  The required match is given by

    f(-1) = -6,

    f(0) = -5,

    f(1) = -4,

    f(2) = -3,

    f(5) = 0,

    f(8) = 3.

    Step-by-step explanation:  We are given a function f(x) defines as follows :

    [tex]f(x)=x-5~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)[/tex]

    We are to match the given values.

    If x = -1,  then from equation (i), we get

    [tex]f(-1)=-1-5=-6.[/tex]

    If x = 0,  then from equation (i), we get

    [tex]f(0)=0-5=-5.[/tex]

    If x = 1,  then from equation (i), we get

    [tex]f(1)=1-5=-4.[/tex]

    If x = 2,  then from equation (i), we get

    [tex]f(2)=2-5=-3.[/tex]

    If x = 5,  then from equation (i), we get

    [tex]f(5)=5-5=0.[/tex]

    If x = 8,  then from equation (i), we get

    [tex]f(8)=8-5=3.[/tex]

    Thus, the required match is given by

    f(-1) = -6,

    f(0) = -5,

    f(1) = -4,

    f(2) = -3,

    f(5) = 0,

    f(8) = 3.

  4. The value of the function f(x) at each point is f(-1) = 5, f(0) = 3, f(1) = 5, f(2) = 11, f(3) = 21 ⇒ A

    Step-by-step explanation:

    Let us use the mapping shown to solve the question

    ∵ f(x) = y

    ∵ x is the domain

    ∵ y is the range

    → From the figure use x from the domain and y from the range, where

       each arrow pointed at the corresponding value y of x

    ∵ x = -1 and the corresponding value of y is 5

    ∴ f(-1) = 5  

    ∵ x = 0 and the corresponding value of y is 3

    ∴ f(0) = 3

    ∵ x = 1 and the corresponding value of y is 5

    ∴ f(1) = 5

    ∵ x = 2 and the corresponding value of y is 11

    ∴ f(2) = 11

    ∵ x = 3 and the corresponding value of y is 21

    ∴ f(3) = 21

    The value of the function f(x) at each point is f(-1) = 5, f(0) = 3, f(1) = 5, f(2) = 11, f(3) = 21

  5. 1. f(x)=1/2x-3     f(x)=1/2x-3

      f(0)=1/2(0)-3   f(6)=1/2(6)-3

      f(0)=-3             f(6)=0

    m=f(b) - f(a)/b - a = 0- (-3)/6 - 0  = 3/6 = 1/2

    2.  f(x) = -x         f(x) = -x

        f(-4) = -(-4)    f(2) = -2

        f(-4) = 4         f(2) = -2

    m=f(b) - f(a)/b - a = -2 - 4/2 - (-4) = -6/6 = -1

    3. f(x) = x^2     f(x) = x^2

       f(-2) = -2^2  f(0) = 0^2

       f(-2) = -4      f(0) = 0

    m=f(b) - f(a)/b - a = 0 - (-2)/0 - (-2) = 2/2 = 1

    4. f(x) = x^3     f(x) = x^3

       f(-1) = -1^3  f(1) = 1^3

       f(-1) = -1      f(1) = 1

    m=f(b) - f(a)/b - a = 1 - (-1)/1 - (-1) = 2/2 = 1

    5. f(x) = 2^x    f(x) = 2^x

       f(0) = 2^0    f(4) = 2^4

       f(0) = 1        f(4) = 16

    m=f(b) -f(a)/b - a = 4 - 0/ 4 - 0 = 4/4 = 1

    i hope this is right, have a good day

Leave a Reply

Your email address will not be published. Required fields are marked *